IMPLEMENTATION OF PRINCIPLES OF UNIVERSALITY IN THE DISTANT LEARNING OF THE COURSE «BASICS OF ALGORITHMIZATION AND PROGRAMMING» WITH THE HELP OF THE IT DISTANCE LEARNING ENVIRONMENT «WEB BAP» - Kovtushenko І.П. (Journal of Information Technologies in Education (ITE), 2010)
The article deals with the role, position and peculiarities of the educational discipline «Basics of Algorithmization and programming» used to train future teachers of informatics. It covers one of the methodic approaches that form the basis of building and using the informational educational environment «Web BAP»